A Comparasion of Scientific Literacy Levels of Gifted and Nongifted Students - Bilge Bal Sezerel; N Nazlı Ateşgöz (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
The number of studies related to scientific literacy has increased dramatically. The widespread adoption of information and technology has made such studies necessary on a global scale. In the 21st century, the most crucial area where competition takes place among countries is considered to be information and technology. It is essential to observe the reflections of digital transformation and innovation in using and disseminating knowledge and technology for students and to take steps in educational fields accordingly. In this study, the levels of scientific literacy (SL) of gifted and nongifted students were compared. The participants of the study consisted of 98 gifted students attending the Education Program of Talented Students (EPTS) and 137 nongifted students attending the EPTS’ project middle school. The Test of Basic Scientific Literacy (TBSL) was used to determine the students' levels of scientific literacy. The test consists of sub-dimensions of the nature of science (NS) and the science-technology-society relationship (STS). The findings of the research showed that the mean scores of both groups in SL, NS, and STS were at a moderate level. To examine whether there were differences in SL, NS, and STS levels between gifted and nongifted students, independent samples t-tests were conducted. The analysis revealed that gifted students had significantly higher scores in SL, NS, and STS compared to nongifted students (p